Main Aspects of the Development of Personal Structures of Consciousness at School Age (Uzbekistan Open Conference, 2025)
This paper examines the development of personal structures of consciousness and explores the characteristics of self-awareness formation during primary school age, adolescence, and youth. Based on the presented data and the results of the study, it is concluded that primary school children largely acquire patterns of male and female behavior spontaneously, while gender education receives very limited attention in educational practice. The study also demonstrates the importance of investigating the processes of gender segregation and convergence, which remain insufficiently explored in pedagogical science.